Priming the representation of Mandarin tone 3 sandhi words. Issue 2 (7th February 2016) - Chien, Yu-Fu; Sereno, Joan A.; Zhang, Jie
ABSTRACT: Phonological alternation poses problems for spoken word recognition. In Mandarin Tone 3 sandhi, a Tone 3 syllable changes to a Tone 2 syllable when followed by another Tone 3 syllable. A traditional phonological account assumes that the initial syllable of Mandarin disyllabic sandhi words is Tone 3 (T3) underlyingly, but becomes Tone 2 (T2) on the surface. In an auditory–auditory priming lexical decision experiment, each disyllabic tone sandhi target word (e.g., chu3-li3) was preceded by one of three monosyllabic primes: a T2 prime (Surface-Tone overlap) (chu2), a T3 prime (Underlying-Tone overlap) (chu3), or a control prime (Baseline condition) (chu1). Results showed that Tone 3 primes (Underlying-Tone) elicited significantly stronger facilitation effects for the sandhi targets than Tone 2 primes (Surface-Tone), with little effect of target frequency. The data are examined in terms of the contribution of underlying representations for models of spoken word recognition.